Information and Communications Security 15th International Conference, ICICS 2013, Beijing, China, November 20-22, 2013. Proceedings - Qing, Sihan; Zhou, Jianying; Liu, Dongmei; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 15th International Conference on Information and Communications Security, ICICS 2013, held in Beijing, China, in November 2013. The 23 regular papers and 6 short papers were carefully reviewed and selected from 113 submissions. The papers are organized in topical sections on system security, Web security and worm detection, cloud storage security, virtualization for cloud computing, trusted and trustworthy computing, authentication and security protocols, intrusion detection and recovery, side channel attacks and defense, engineering issues of crypto, cryptanalysis, attribute-based encryption, and cryptographic primitives and applications.
System Security -- Web Security and Worm Detection -- Cloud Storage Security -- Virtualization for Cloud Computing -- Trusted and Trustworthy Computing -- Authentication and Security Protocols -- Intrusion Detection and Recovery -- Side Channel Attacks and Defense -- Engineering Issues of Crypto -- Cryptanalysis -- Attribute-Based Encryption -- Cryptographic Primitives and Applications.
Keywords: Computer science; Data protection; Data encryption (Computer science).; Computer software; Computer Science; Data Encryption; Systems and Data Security; Algorithm Analysis and Problem Complexity